Analyzing the Influence of Sustainable Entrepreneurial Orientation on Sustainable Business Performance through Competitive Advantage of SMEs in Jakarta, Indonesia - Febriyantoro, Mohamad Trio; Zulkifli, Zulkifli (International Journal of Business, Law, and Education, 2025)
In the era of globalization, companies face various challenges and risks, including competition. To survive in this constantly changing business environment, it is important to identify and address both opportunities and threats. The aim of this study is to investigate the impact of sustainable entrepreneurial orientation on business performance in SMEs, with competitive advantage acting as a mediating variable. The research surveyed 325 SME entrepreneurs in Jakarta City. The data was analyzed using the Structural Equation Modeling with Partial Least Square (SEM PLS) approach. The findings demonstrate that sustainable entrepreneurial orientation has a significant effect on business performance in SMEs. In SMEs, there is a significant relationship between sustainable entrepreneurial orientation and competitive advantage, as well as between competitive advantage and business performance. The relationship between sustainable orientation and business performance is mediated by competitive advantage.